Edward Burtynsky : l’oeil d’un coloriste sur le sublime contemporain - Chalifour, Bruno (Ciel variable, 2006)
Abstract This article addresses the new work by Edward Burtynsky as it was presented, in part, at the Brooklyn Museum of Art. In this exhibition, twenty-four images on contemporary China were added to the touring exhibition Manufactured Landscapes, at the Charles Cowles Gallery in New York City in the fall of 2005, and in a book called China published simultaneously by Steidl. The project China, on which Burtynsky's efforts have been concentrated for the past five years, encompasses the characteristics of Burtynsky's style as they have been sketched out over the past two decades. China confirms the concerns developed in Manufactured Landscapes; striking in this work, however, is the emergence of a humanist and social conscience.